Endobronchial ultrasound-guided transbronchial needle aspiration rinse fluid polymerase chain reaction in the diagnosis of intrathoracic tuberculous lymphadenitis. Issue 3 (4th March 2017) - Boonsarngsuk, Viboon; Saengsri, Siriwan; Santanirand, Pitak
Abstract: Background: Intrathoracic tuberculous (TB) lymphadenitis is a diagnostic challenge to the clinician. Although endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) can obtain a sample from the affected lymph node, the diagnosis of TB lymphadenitis by cytopathology remains inaccurate. Objective: To evaluate the efficacy of EBUS-TBNA rinse fluid TB polymerase chain reaction (PCR) assay for the diagnosis of intrathoracic TB lymphadenitis. Methods: A retrospective study was conducted on 102 patients who underwent EBUS-TBNA for diagnostic evaluation of intrathoracic lymphadenopathy. EBUS-TBNA specimens were evaluated by cytopathological examination. Rinse fluid of the needle was routinely submitted for acid-fast bacillus (AFB) staining, mycobacterial culture, and TB-PCR using the Anyplex TM MTB/NTM real-time detection kit. Results: Of 102 patients, 16 were diagnosed with intrathoracic TB lymphadenitis by either microbiology, cytopathology, or on clinical grounds. The sensitivity, specificity, positive predictive value, and negative predictive value of rinse fluid TB PCR assay were 56.2%, 100.0%, 100.0%, and 92.5%, respectively. Using the area under the ROC curve (AUC) as a measure of a diagnostic performance, TB-PCR had the highest AUC, compared with mycobacterial culture, AFB smear, and finding of necrotizing granulomatous inflammation (0.78, 0.75, 0.56, and 0.72, respectively). A combination of TB PCR, mycobacterial culture, and finding of necrotizing granulomatous inflammation provided the best diagnostic performance (sensitivity, specificity, positive predictive value, negative predictive value, and AUC of 75.0%, 100.0%, 100.0%, 95.6%, and 0.88, respectively). Conclusions: EBUS-TBNA rinse fluid TB-PCR is useful in the diagnosis of intrathoracic TB lymphadenitis. Combining TB-PCR with mycobacterial culture and cytopathological findings improved the diagnosis performance.